Noninvasive Hemodynamic Assessment as Part of Preoperative Examination of Patients with Colorectal Cancer - M. I. Aleksandrov; E. A. Spiridonova; S. N. Perekhodov; I. G. Bobrinskaya; G. V. Esin; M. B. Lagutin; L. F. Goncharov; D. I. Tsyganov (Общая реаниматология, 2014)
Objective: to determine the capacities of a noninvasive hemodynamic study in patients with colorectal cancer within a preoperative anesthesiological examination. Subjects and methods. The hemodynamic status was preoperatively analyzed in 97 patients (46 men and 51 women) with colorectal cancer. Their mean age was 67.59±9.48 years. The POSSUM intraoperative risk scores were 20.20+3.2. Central hemodynamics was preoperatively assessed in all the patients, by applying a «Computerized Diamant System for Monitoring the Cardiorespiratory System and Tissue Hydration» (Saint-Petersburg, Russia — Registration Certificate ФСР No 2008/03201 dated 22 August, 2008).Results. The non-invasive hemodynamic study can supplement a preoperative examination in patients with colorectal cancer. The patients with colorectal cancer were diagnosed as having hypodynamic and eudynamic circulation in 43.3 and 56.7% of the cases, respectively. The age of the patients was not established to have a significant impact on their hemodynamic status, which confirms that it is expedient to make perioperative multifactorial risk assessment.